THE NEED FOR NEEDS ANALYSIS IN CURRICULUM DEVELOPMENT IN ESP COURSE: A REFLECTION ON CURRICULUM DEVELOPMENT IN INDONESIA - Mahardika, A.A. Ngurah Yudha Martin (Jurnal Bahasa Lingua Scientia, 2014)
Curriculum development as the guide to instructional implementation should be able to ‘bridge the gaps’ of the needs among the parties in teaching learning process. Needs analysis is then a crucial step in curriculum development. It includes the needs of the intitution, the target needs, and for the most, the learners’ needs. Indonesian curriculum may change as the result of the current situation or policy, yet the concern remain the same, that is to identify needs and accomodate those needs. Introduction on curriculum development, a brief review on ESP, discussion on needs analysis, and reflection of the curriculum development in Indonesia related to needs analysis would be delivered in this article.